PRODUCTIVITY AND EFFICIENCY ANALYSIS OF PURSE SEINE FISHERIES IN THE COASTAL WATERS OF BULELENG - Irwansyah, M. Rudi; Dharmayasa, I Putu Arya; Vijaya, Diota Prameswari (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Indonesia's vast marine territory, encompassing 70% of its total area with 104,000 km of coastline and 5.8 million km² of waters, presents significant economic opportunities for coastal communities. Bali Province, with its 9,211.76 km² marine area and substantial fishing population of 68,925 people, contributes meaningfully to Indonesia's fisheries sector. This research specifically examines purse seine fishing operations in Seririt District, Buleleng Regency, where three active fishermen groups employ this method. The study addresses the critical challenge of balancing fishing productivity with marine ecosystem conservation, aligning with Blue Economy principles for sustainable marine resource management. Our research, conducted from February to November 2024, provides comprehensive analysis of purse seine fishing operations through three interconnected objectives: (1) calculating fishing productivity metrics, (2) identifying key production factors influencing catch yields, and (3) evaluating technical and economic efficiency of purse seine operations. Using robust analytical methods including productivity assessments, multivariate production factor analysis, and efficiency measurements across three fishermen groups, we establish evidence-based benchmarks for sustainable purse seine operations. The findings reveal optimal input combinations that maximize economic returns while minimizing environmental impacts. This research delivers actionable insights for policymakers and fishing communities, supporting the development of targeted regulations that promote sustainable fishing practices while maintaining the economic viability of coastal livelihoods in Buleleng's waters.